The Role of the Nucleus of the Solitary Tract in Gustatory Processing - Bradley, Robert M (Frontiers in neuroscience, 2007)
The nucleus of the solitary tract (NST) provides an essential brainstem relay for three cranial nerves, coordinating highly complex sensory information. While other functions of the NST have received attention, its role in gustatory processing has received little. This work is the first reference on the NST devoted exclusively to gustatory processing. Compiling past and current research into a single volume, it documents the anatomy of the NST, explores the properties of synaptic transmitters and neurons in the NST, compares the gustatory NST with the caudal NST, and considers the challenge involved with identifying NST neural circuits, as well as other areas needing research.